Socioeconomic Aspects of Muslim Child Laborer Involved in Informal Public Transport in Bangladesh - Najeeb Razul A. Sali; Hasnain Ahammad (Research Parks Publishers, 2022)
Many children were involved in economic actions explicitly in the Informal Public Transport sector in Dhaka, Bangladesh. They were traced working under incomputable exploitive workspace, suffering from exceptional health conditions, and deprived of what they required and deserved. These children are deprived of equitable or stable wages equivalent to the extent of their deeds. Furthermore, holidays, health facilities, and recreational activities were specifically non-existent for these children. This present study aimed to explore the child labourer’s status in terms of socio-economic deprivation, health, and abuses, which are deliberated as significant in computing the welfare of life. In a descriptive way, the quantitative research method was utilised, compiling data with a sample size of 45 respondents among child labourers. From the exploration of the data, it was vindicated that child labourers were viciously deprived of their socio-economic rights affirmed them in the resolution on the rights of child (CRC) through in adequate remunerations, amenities, bonuses, corporal, psychological, and pecuniary abuse. The partaking of children in the Informal Public Transport sector deprived them of the opportunities for attaining education, skills, and training indispensable for being furnished in the ruthless circumstances of contemporary society. Few researches were wielded in the past whilst they did not dig up the amalgamation of economic evolution, veneration for labors criterion, and social protection, along with a better cognition of the needs and rights of children. This study would assist in bringing a significant amputation in socio-economic deprivation of child labor. Data were also compiled from primary and secondary sources, relevant and related articles, peer-reviewed journals, and books.